Gugatan Ahli Waris atas Harta Hibah Perspektif Fikih Islam - Saadal Jannah; Akrama Hatta; Winda Sari Agustini (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
This study aims to identify and understanding the claim of the heirs on the assets of the grant in the perspektif of Islamic jurisprudence. This research uses qualitative research with library research methods. The results of the study found that the majority of scholars forbade a person to withdraw his grant property, except for the grant of a father to his child. As for when the heir want to sue the assets of the grant, then there are two conditions; first, the heirs may sue the assets of the grant if the property being donated is the entire property of the grantor. second, the heirs may not sue the grant property if it is not the entirety of the property being donated. Scholars also differ on the amount of property that can be donated. Many scholars are of the opinion that it is permissible to donate all of their wealth (without limits) to others, because the amount of the grants is not explained ini the texts. Meanwhile, Ibn Hasan and some of the Hanafi school of pentahqiq argue that it is not legal to donate all their wealth even if it is in goodness.